Do We Talk Too Much? - Emanuel Vespa; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We consider the trade-off between talking and listening in a laboratory experiment where two team members need to coordinate on the use of an information channel. Each team member indicates their preference to "talk" and share her own information with her teammate, or to "listen" and obtain knowledge of the teammate's information. The nature of the information varies across treatments. For stylized urns-and-balls treatments, we formalize a version of the "hard-easy effect" of over- and under-confidence: players talk more in situations where information is relatively precise – not only for the talker but also for the listener. Indeed we find that a more precise information structure induces a higher talking frequency, with a difference of 5 percentage points, relative to a baseline of 48 percent. The game-theoretic equilibrium, with rational expectations, predicts no such treatment effect. In treatments where information arises from real-world contexts, the hard-easy effect on the talking frequency is even stronger, at about 13 percentage points, relative to a baseline of about 38 percent.
Keywords: 330